Perwarnaan Pseudo Ultrabunyi Dan Analisa Tekstur Dengan Menggunakan Pendekatan Logik Fuzzi Bagi Membezakan Sistik Dan Ketulan Padat - Ariffin, Fairul (Universiti Sains Malaysia, 2006)
There are two type of tumor identified in human body that are cystic and solid. In order to detect and identify this tumor, a few methods have been used and the common methods are mammogram and ultrasound. Although mammogram has been approved to be effective in usage but ultrasound is likely to have its own specialty. In other word ultrasound is a method common that is to be harmless to the physiology of human being. The test is done continuously for purpose of detail analysis and observation. Computers are widely used by radiologist to manipulate and describe the ultrasound image. The future of the medical development is highly depends on the modern technology applications like data sending, and processing visual facilities. This project is implemented to automatically analyze ultrasound image in which it will replicate the analysis process that has been done by the radiologist to the image. This project will test the effectiveness of changing the monochrome image to color image using pseudocoloring technique. This technique will expose the ultrasound image for the essential information analysis purpose. This technique will also show the grey level value the chosen coordinate. Therefore there is another technique used to analyze the texture of the ultrasound image using fuzzy logic. With this technique, solid and cystic can be differentiated based on frequency of the gray level value from the image.